Konsep Pendidikan Anak Perspektif Luqmanul Hakim - Mujib, Ahmad (SAP (Susunan Artikel Pendidikan), 2024)
Children's education in the family is an inherent obligation and cannot be ignored. The success of a child's education is closely related to the educational patterns that first shape a child's character. This research aims to find an Islamic concept of children's education for parents and educators in educating children. This research uses library research methods, conducted in July-December 2023, the primary data source is the Al-Qur'an Surah Luqman: 12-19, and the secondary data sources are tafsir books, fiqh and relevant articles or journals, Data analysis was carried out using descriptive analysis techniques. This research concludes that the concept of children's education according to Luqmanul Hakim is as follows: children's education must be based on wisdom from their educators, using mau'izhah and testament as a method of delivering material, fostering a sense of gratitude, giving birth to an attitude of filial piety towards both parents, fostering an attitude of responsibility and independence for children in various aspects, enjoining good deeds and prohibiting being haughty and arrogant.